2018
DOI: 10.2478/pfs-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Species in section Peltidea (aphthosa group) of the genus Peltigera remain cryptic after molecular phylogenetic revision

Abstract: Closely related lichen-forming fungal species circumscribed using phenotypic traits (morphospecies) do not always align well with phylogenetic inferences based on molecular data. Using multilocus data obtained from a worldwide sampling, we inferred phylogenetic relationships among five currently accepted morphospecies of Peltigera section Peltidea (P. aphthosa group). Monophyletic circumscription of all currently recognized morphospecies (P. britannica, P. chionophila, P. frippii and P. malacea) except P. apht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
(110 reference statements)
1
26
0
Order By: Relevance
“… O’Brien et al (2013) found five different Nostoc phylogroups (I, III, IV, V, and VI) in association with species of the three trimembered sections of Peltigera , each species showing a different degree of specificity toward Nostoc phylogroups. An unusually high level of reciprocal specificity between Nostoc and P. malacea was detected by O’Brien et al (2013) , which was confirmed by Miadlikowska et al (2018) based on more specimens and additional loci. Based on a multi-locus phylogenetic study, Miadlikowska et al (2018) also found that several mycobiont clades within section Peltidea could potentially represent new species.…”
Section: Introductionmentioning
confidence: 55%
“… O’Brien et al (2013) found five different Nostoc phylogroups (I, III, IV, V, and VI) in association with species of the three trimembered sections of Peltigera , each species showing a different degree of specificity toward Nostoc phylogroups. An unusually high level of reciprocal specificity between Nostoc and P. malacea was detected by O’Brien et al (2013) , which was confirmed by Miadlikowska et al (2018) based on more specimens and additional loci. Based on a multi-locus phylogenetic study, Miadlikowska et al (2018) also found that several mycobiont clades within section Peltidea could potentially represent new species.…”
Section: Introductionmentioning
confidence: 55%
“…We assembled a dataset of Peltigera-Nostoc interaction pairs summing up all information from the literature for which we could confidently assess the identity of the Peltigera species and Nostoc phylogroups or haplotypes (Chagnon et al, 2018;Lu et al, 2018;Magain, Miadlikowska, Goffinet, et al, 2017a;Magain, Miadlikowska, Mueller, et al, 2017b;Magain et al, 2018;Miadlikowska et al, 2014Miadlikowska et al, , 2018O'Brien, Miadlikowska, & Lutzoni, 2005;O'Brien, Miadlikowska, & Lutzoni, 2013;Pardo De la Hoz et al, 2018). The total dataset consisted of 1,026 thalli, or interaction pairs, representing 155 Peltigera species and 95 Nostoc phylogroups or haplotypes (Tables S1 and S2).…”
Section: Sample Acquisition and Interaction Network Inferencementioning
confidence: 99%
“…To infer a phylogeny for the entire genus Peltigera, we gathered published data from all currently validated species (Chagnon et al, 2018;Magain, Miadlikowska, Goffinet, et al, 2017a;Magain, Miadlikowska, Mueller, et al, 2017b;Magain et al, 2018;Miadlikowska et al, 2014Miadlikowska et al, , 2018Pardo De la Hoz et al, 2018) for seven loci (ITS, nrLSU, β-tubulin, RPB1, COR1b, COR3, COR16). We selected one representative per species with the highest number of sequenced loci, or two representatives per species when sets of available loci were mostly non-overlapping between two specimens of a species.…”
Section: Phylogeny Of the Genus Peltigeramentioning
confidence: 99%
See 2 more Smart Citations